The Role of Co-Operative Enterprises - Pečiuliauskas, Gintautas (Ekonomika, 2000)
The matters of evaluations of the cooperation’s importance and of the co-operative enterprises role are analysed in the article.It is stressed, that the number of co-operative enterprises and the number of members of co-operative enterprises are not suitable to use as indicators to define the importance of co-operation and the role of co-operative enterprises. The author of the article emphasis as well. that the data about market share of product’s (services) occupied by co-operative enterprises properly demonstrate a real situation about importance of co-operation and role of co-operative enterprises.The suggestions for combined evaluation are made according to the results of the research on the importance and the role of co-operation in some West Europe countries.The suggestions for Lithuanian national economy development are made on the oasis of that evaluation.